Engineering manipulation at nanoscale: further functional specifications. Issue 3 (1st March 2019) - Mekid, Samir; Bashmal, Salem
Abstract : Purpose: Novel nanomaterials and nano-devices require further functional aspects that can be designed and supported using new nanomanipulation techniques allowing specific functions at the design phase. The nano-manipulator becomes a key instrument for technology bridging sub-nano to mesoscale. The integration of various operations in nano-devices requires sub-nanometer precision and highly stable manipulator. This paper aims to review various design concepts of recent nanomanipulators, their motion characteristics, basic functions, imagine and automation with control techniques for the sake of establishing new design features based on recent requirements. Design/methodology/approach: The paper reviews various existing nanomanipulators, their motion characteristics, basic functions, imagine and automation with control techniques. This will support precision machine design methodology and robotics principles. Findings: The availability of a nano-precision instrument with integrated functions has proved to be extremely helpful in addressing various fundamental problems in science and engineering such as exploring, understanding, modeling and testing nano-machining process; exact construction of nano-structure arrays; and inspection of devices with complex features. Originality/value: New functional specifications have emerged from this review to support the design and make of new advanced nanomanipulators with more features availability to support manipulation within the same reference datum needed for research and education.